Intra-rater and inter-rater reliability of 3D facial measurements - Olmedo-Nockideneh, Isabel Rosalene, author; Rosecrance, John, advisor; Brazile, William, committee member; Gutilla, Margaret, committee member (Colorado State University. Libraries, 2023)
The purpose of this study was to assess the intra- and inter-rater reliability of a three-dimensional (3D) measurement system for determining the facial anthropometrics of 2,000 individuals. Intra-rater reliability is the degree of agreement among repeated administrations of a measurement system performed by a single rater and inter-rater reliability is the degree of agreement among independent raters who rate, code, or assess the same phenomenon using the same measurement system. Research studies that require the use of novel measurement systems by several raters must first establish that the phenomenon being measured have acceptable levels of both intra- and inter-rater reliability. Assessments of novel measurement systems are useful in refining the measurement tools given to raters by determining if a particular scale is appropriate for measuring a specific phenomenon. The present study was one facet of a larger anthropometric study of 2,000 facial scans, which investigates the demographic variables that may account for differences in facial size and shape. For this reliability study, a random sample of 30 facial scans was hand-digitized by four coders. The randomized sample was used to assess the intra- and inter-rater reliability of 28 facial anthropometric landmarks. The intraclass correlation coefficient was used to assess rater reliability. The results of the study indicated generally good inter-rater reliability and a steady improvement in both intra- and inter-rater reliability with greater experience. There are no conflicts of interest or a current funding source regarding this study. This study will impact environmental and occupational health by contributing a reliability study to my colleagues.